Between the Cathedrals of Vilnius and Cracow: Some Historical Details in the Background of the Early Cult of St Casimir (Second and Third Decades of the Sixteenth Century) - Čiurinskas, Mintautas (Senoji Lietuvos literatūra, 2024)
Although the literature on the cult of St. Casimir is quite extensive, not all of the historical circumstances of this cult have been given the attention they deserve. The accumulated material of the sources, including those that have not been used in research so far, allows supplementing the history of the beginnings of the cult with new insights and observing the unfolding of the connections with important events in the history of Lithuania and Vilnius at the time. One of these connections (with schematic references to two capitals) is the tradition of public life in Vilnius and Cracow, the cooperation and a certain amount of rivalry in the celebration of the royal saint buried in Vilnius and in the pursuit of the official recognition of the saint, i.e., his canonisation. After it had been achieved (1602) and celebrated with pomp and circumstance in Vilnius (1604), the number of writings dedicated to the saint increased rapidly. One of the motifs reflected even in the poetry of the time is the rivalry between Vilnius and Cracow. In interpreting this and other themes in Casimirian literature, fresh and closer examination of the prehistory, especially the earliest period of the cult marked by the earliest attempts at canonisation, is important. The article focuses on this particular aspect by looking at the historical background of the cult of the second-third decades of the sixteenth century and at the reflection of some important events in the writings of the time directly or indirectly related to the future saint. The second part of the diptych of articles will deal with the texts from the beginning of the seventeenth century.